2019
DOI: 10.1007/s42773-019-00013-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sole and combined application of biochar, organic and chemical fertilizers on wheat crop yield and water productivity in a dry tropical agro-ecosystem

Abstract: Agriculture under changing climate scenario is facing major challenges of water scarcity and resource imbalances. Crop water productivity (WP) may act as an indicator of crop responses to water limitation. Organic amendments such as biochar and manure application to soil are suggested for improving soil quality and reducing water requirements from agricultural sector. However, studies exploring the impact of biochar as sole or in combination with organic and/or chemical fertilizers on WP in dry tropical agro-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…The surface functional groups, which include aliphatic, aromatic, hydroxyl, carboxyl, carbonyl, amido, and azyl groups, could be determined by FT-IR (Uchimiya et al 2013), X-ray photoelectron spectroscopy (XPS) (Singh et al 2019), and NMR (Cao et al 2011). Some studies have investigated surface functional groups on biochars, such as carboxyl, carbonyl, phenolic -OH, and ester groups (Mao et al 2012;Rao et al 2011).…”
Section: Surface Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The surface functional groups, which include aliphatic, aromatic, hydroxyl, carboxyl, carbonyl, amido, and azyl groups, could be determined by FT-IR (Uchimiya et al 2013), X-ray photoelectron spectroscopy (XPS) (Singh et al 2019), and NMR (Cao et al 2011). Some studies have investigated surface functional groups on biochars, such as carboxyl, carbonyl, phenolic -OH, and ester groups (Mao et al 2012;Rao et al 2011).…”
Section: Surface Chemistrymentioning
confidence: 99%
“…Biochar is a stable carbon-rich solid product obtained by pyrolysis of biomass under an oxygen-limited environment (Chen et al 2008;Lehmann 2007;Xiao et al 2018). Due to its inert carbon matrix, rich surface oxygen-containing functional groups, high surface area, and developed pore structure, biochar has shown great potential in carbon sequestration, greenhouse gas (CO 2 , N 2 O, and CH 4 ) emission reduction (Woolf et al 2010;Wang et al 2019b), soil improvement (Lehmann et al 2011;Weng et al 2017;Palansooriya et al 2019) and crop yield increase (Khan et al 2013;Singh et al 2019), which received increasing attention from scientists and policy makers around the world. In the terms of environmental remediation, Chen et al (2008) systemically investigated the sorption of organic pollutants by biochar pyrolysis at different temperatures, and they found that the adsorption mechanisms of biochars were evolved from partitioning-dominant at low pyrolytic temperatures to adsorption-dominant at higher pyrolytic temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, we could clearly delineate and provide clearer information of the contribution of each of the factors (biochar and fertiliser) to maize growth and yield. This becomes imperatives since the modelling approach is lagging in the growing body of knowledge on the roles of individual and combined application of biochar and inorganic fertiliser in improving crop growth and yield under water limiting conditions (Akhtar et al 2014;Agbna et al 2017;Singh et al 2019) and salinity stress (Kazemi et al 2019). In all irrigation treatments, the canopy cover (CC) was well predicted in the biochar-treated plots during the calibration and validation.…”
Section: Discussionmentioning
confidence: 99%
“…This has intensified the study of crop (maize) water productivity under deficit irrigation (Oktem 2008; El-Hendawy and Schmidhalter 2010; Karimi and Gomrokchi 2011;Talaat 2020). Moreover, soil amendments such as manure and inorganic fertiliser are being used to complementarily improve crop productivity in deficit irrigation practice (Reddy et al 2009;Singh et al 2019). But organic manure and inorganic fertiliser easily mineralise in soils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation